Male perceptions of family planning in four sub-Saharan African countries: Evidence from demographic and health surveys - Friday Okonofua; Lorretta Favour Ntoimo; Wingston Ng’ambi; Adamson Muula; Ousmane Ndiaye; Daprim Ogaji; Vivian Onoh; Rose Ugiagbe; Hadiza Galadanci; Rosemary Ogu; Alexandre Delamou (Heliyon)
Sub-Saharan African countries have the lowest combined contraceptive prevalence rates among the six world regions, partly attributable to men's low participation in family planning activities. The objective of this study was to compare the prevalence and determinants of male perceptions relating to family planning in Malawi, Guinea, Nigeria, and Senegal, and to learn lessons for improving male participation in family planning in the four countries. We analyzed male recode datasets from the most recent Demographic and Health Surveys in the four countries. The total sample size was 28,271 men, consisting of 4,117 from Guinea, 7,478 from Malawi, 13,311 from Nigeria, and 3,365 from Senegal. The results showed poor perceptions of family planning among males in the four countries overall, with nearly 56 % of the men demonstrating negative perceptions of family planning. Men in Guinea and Nigeria had the lowest positive perceptions of family planning as compared to Malawi and Senegal, but when subjected to multivariable logistic regression, only Guinea remained the country with the lowest positive male perception of family planning. The predictors of positive perceptions of family planning were older men, higher educational levels (in all countries but Guinea), a higher household wealth index (but not in Malawi), previous use of contraceptives, previous use of the internet and the media, and being married. By contrast, religious affiliation and preference for more children diminished the odds of positive perception. We conclude that there is a poor perception of family planning among men in Guinea, Senegal, Nigeria, and Malawi, with Guinea showing the most deprived results as compared to the other countries. Efforts to include male participation in policies and programs relating to family planning will increase the uptake of contraceptives and promote overall health and development outcomes in these four countries, with implications for other sub-Saharan African countries.